Penyuluhan kesehatan tentang diet pada pasien hipertensi di Kecamatan Banyuresmi Kab. Garut - iin Patimah; Rudy Alfiyansah; Eldessa Vava Rilla; Engkus Kusnadi; Wahyudin; Aceng Ali Awaludin (Jurnal Pengabdian Masyarakat DEDIKASI, 2020)
Hypertension is persistent blood pressure where the systolic blood pressure is above 140 mmHg and the diastolic blood pressure is above 90 mmHg. In the elderly population, hypertension is defined as a systolic blood pressure of 160 mmHg and a diastolic pressure of 90 mmHg. With increasing age, the structure and function of the human body system changes, be it physical, mental, social and emotional. This will affect various aspects of life in old age. The purpose of this community service in addition to wanting to know the number of people with hypertension, improving the health status of residents in the Banyuresmi Garut District and providing counseling education about the dangers of hypertension. The methods used are health checks, blood sugar checks, uric acid, cholesterol and blood pressure checks. And health promotion related to diet in people with hypertension. This counseling activity is an activity that has a positive impact because it can increase knowledge to the elderly about hypertension in the Banyuresmi District, Garut Regency.